Tracing the role of plant proteins in the response to metal toxicity: a comprehensive review - Jain, Shruti (Plant Signal Behav, 2018)
Plants are sessile in nature, but are capable to evade from high level concentration of heavy metals like Cd, Hg, Cu, through various metabolic pathways. Some of the pathways regulate normal metabolism in plants, whereas others are required for for their survival under metal toxicity. Different plant proteins act as transporters to transfer metal from one organelle to the other and further eliminate it out from the plants. Initially, exposure of heavy metals/metalloids to plants lead to over expression of proteins which in turn stimulate other stress-related genes. Further, they activate signalling mechanism like MAPK cascade, Cd-Calmodulin signalling pathway, and oxidation signalling pathway that lead to generation of ROS (reactive oxygen species). Once these ROS (highly unstable) are formed, they generate free radicals which react with macromolecules like proteins and DNA. This has negative impact on plant growth and leads to ageing and, eventually, cell death. The uncontrolled, destructive processes damage plants physiologically and ultimately lead to oxidative stress. Activation of antioxidant enzymes like SOD (superoxide dismutase) and CAT (catalase) allows plants to cope under oxidative stress conditions. Among plant proteins, some of the antioxidant enzymes like glutathione, and APX (ascorbate peroxidase) play defensive roles against abiotic stress in plants. Chaperones help in protein folding to maintain protein stability under stress conditions. With this background, the present review gives a brief account of the functions, localization and expression pattern of plant proteins against metal/metalloid toxicity. Moreover, the aim of this review is also to summarize the cutting edge research of plant protein and metal interfaces and their future prospects.